SPATIAL PATTERNS OF TERMITE MOUNDS IN GUATEMALA - RIGHETTO, Ana Julia; FRADE, Djair Durand Ramalho; NAKAMURA, Luiz Ricardo; RAMIRES, Thiago Gentil; BAUTISTA, Ezequiel Abraham López; RIBEIRO JUNIOR, Paulo Justiniano (Brazilian Journal of Biometrics, 2017)
Studying and understanding the behaviour of certain kinds of insects and/or pests in a plantation is critical in any region, since it gives subsidies for possible public and/or private policies if any intervention is needed. In this context, many different studies are available in a wide literature, e.g. about spatial patterns of termite mounds, that cannot be extrapolated for everywhere. Since each region has individual needs, it is reasonable to conduct different studies in specific areas of interest. In this paper we studied spatial patterns of termite mounds in a teak plantation in the northern of Republic of Guatemala, splitting the data set according to termite mounds sizes (small, medium and large) and analysing their individual and cross patterns. For individual patterns we noticed that when only small termite mounds or when all termite mounds were considered an aggregation distribution throughout the studied region was detected, while large termite mounds presented this pattern only in a specific area and medium ones showed a regularity pattern in the whole region. For cross patterns no attraction or inhibition relationships were observed.